A study conducted among young women living in specific locations of Honavar, Uttara Kannada, to evaluate their attitudes and knowledge about women abuse. With a view to organize a Mass Health Education Programme - M.Thirumurugan; Binita Kumari; B.N. Vaishnavi; Rashmita Dsouza; Roshni Sara Philip; Muskan Nasi; Kavyanjali Wadd; Anju Thomas; Aparna Shaji; Anita Kumari (International Journal of Brain Sciences, 2024)
Worldwide and regional projections of violence against women indicate More than 25% of women in relationships between the ages of 15 and 49 report having experienced physical or sexual abuse at least once in their lifetime (since they were 15). Up to 38% of all female killings globally are the result of intimate relationship violence. Apart from domestic violence, 6% of women worldwide report experiencing sexual assault at the hands of someone other than their relationship, yet there is comparatively little information available regarding non-partner sexual violence. Most of the intimate relationship and sexual violence against women is committed by men. The study adopted a descriptive research design and a quantitative research approach. 100 young women were selected by purposive sampling technique from Haldipur, Pavinkurva and Karki at Honavar. Data was collected with a 20 structured questionnaire and five-point rating scale with 34 statements to measure the knowledge and attitude level on women abuse. Data analyzed by testing the frequency, percentage distribution, chi-square test to determine the significant association between the knowledge and attitude level with selected demographic variables. Findings of overall knowledge level show that there is only 1(1%) has excellent knowledge, 42(42%) has good knowledge, 47(47%) has average knowledge and 10(10%) has poor knowledge. It shows that the maximum number of subjects had average knowledge in the study. Overall attitude level shows that only 15(15%) are having very positive attitude, 65(65%) are having positive attitude and 20(20%) are having neutral attitude. The Present study was concluded as majority of the young women in the selected areas at Honavar are having average knowledge in the study and only few are having neutral attitude . The researchers recommend conducting similar study among larger and different population with randomized sampling in different settings to make broad generalization.
Keywords: Assess; Knowledge; Mass health education programme; attitude; women abuse